2007
DOI: 10.1111/j.1570-7458.2007.00635.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of pheromone lure and trap design for monitoring the fir coneworm, Dioryctria abietivorella

Abstract: The major components of the sex pheromone of Dioryctria abietivorella (Groté) (Lepidoptera: Pyralidae) were recently identified as (9 Z ,11 E )-tetradecadien-1-yl acetate (9 Z ,11 E -14:Ac) and a polyunsaturated, long-chain hydrocarbon (3 Z ,6 Z ,9 Z ,12 Z ,15 Z )-pentacosapentaene (C25 pentaene). The optimal ratio of these components and the role of potential minor components were not fully determined in the initial short report on the pheromone's identification. We tested different ratios of the two major co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 18 publications
2
33
0
Order By: Relevance
“…For example, in British Columbia, male D. abietivorella were attracted to a 1:10 ratio of Z9,E11Ð14:Ac and pentaene, with no effect from the addition of Z9 Ð 14:Ac (Strong et al 2008). In contrast, Z9 Ð14:Ac was essential for eliciting attraction of D. abietivorella to the same combination of Z9,E11Ð14:Ac and pentaene in Quebec (Grant et al 2009).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…For example, in British Columbia, male D. abietivorella were attracted to a 1:10 ratio of Z9,E11Ð14:Ac and pentaene, with no effect from the addition of Z9 Ð 14:Ac (Strong et al 2008). In contrast, Z9 Ð14:Ac was essential for eliciting attraction of D. abietivorella to the same combination of Z9,E11Ð14:Ac and pentaene in Quebec (Grant et al 2009).…”
Section: Discussionmentioning
confidence: 88%
“…Lures were prepared by loading compounds onto gray rubber septa (11 mm; The West Co., Lionville PA) in 100 l of hexane, with butylated hydroxytoluene and Sumisorb 300 (each 5 mg/ml) added as stabilizers to the solutions. These adjuvants had no effect on trap catches of D. abietivorella (Strong et al 2008). Commercial lures for D. amatella (SPC) were obtained from APTIV Inc. (Portland OR).…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Although this difference was not significant here, Allison and Cardé (2006) found that the ratio of pheromone components in a pyralid moth (Cadra cautella (Walker)) changed with female age, and suggested that males could use this to assess the reproductive value of females, which declined markedly with age. If this is the case in M. privata, it may explain why significantly more males were caught in traps baited with a lower ratio of C19: C21 triene (16:1) than in traps baited with a ratio closer to the average found in females (33:1) (see also : Szöcs et al 1993;Strong et al 2008).…”
Section: Discussionmentioning
confidence: 95%
“…The observed antagonistic effect in D. abietella males to 9 Z ,12 E ‐14:OAc may be explained by the fact that it stimulates the same receptor as 9 Z ‐14:OAc (Löfstedt et al 1983). The effect of 9 Z ,12 E ‐14:OAc on male attraction also has been evaluated for D. abietivorella from western North America (Strong et al 2008). No antagonistic effect was observed, but the absolute amount (2 μg), as well as the relative amount (1% of 9 Z ,11 E ‐14:OAc in blend) of the compound applied to dispensers were lower than those used in the present study with D. abietella (3–30 μg; 3‐30% of 9 Z ,11 E ‐14:OAc in blend) .…”
Section: Discussionmentioning
confidence: 99%